Grammatical Errors in Speaking Made by the Third Year English Department Students STKIP Abdi Pendidikan Payakumbuh - Hervina, Hervina (AT-TALIM, 2014)
Speaking is important skill in the language learning. Many people assumed that study the language must be able to speak using the language. Besides that, language is a system of understanding to communicate with others. The researcher found out the error and hopefully it can be reflection in learning English. The method of this research is qualitative research. It is based on the research focus; to analyze the grammatical errors of English department studentsâ of STKIP Abdi Pendidikan Payakumbuh. The methods used by the researcher to get the data were observation, interview, and documentation. There were three activities on data analysis; data reduction, data display, and conclusion drawing/ verification. The result shows that the students have not mastered the use of verb groups. It can be seen from the number of the errors made. Although they had been taught about it before, they were still confused which one to use when making a grammatical sentence.Â Copyright Â© 2014 by Al-Talim All right reserved